Characteristics tests of cerebrospinal fluid cytology, chemistry and bacteriology in invasive paediatric bacterial meningitis in Madagascar - Rahajamanana, Lalaina V.; Andriatahiana, Dera S.; Andrianjakasolo, Paulin; Raboba, Liliane J.; Ratovohery, Andry N.; Rasamindrakotroka, Andry (International Journal of Research in Medical Sciences, 2022)
Background: Paediatric bacterial meningitis is a major public health problem. CSF laboratory analysis is the key element to confirm the disease but remains difficult to access by clinicians or patients in low-resource settings. We described CSF biological tests results in invasive paediatric bacterial meningitis at the University Hospital Mother and Child of Tsaralalàna (CHUMET) in Madagascar. Methods: In this retrospective and descriptive study from January 2013 to December 2018, all CSF samples that were confirmed for bacterial meningitis by triplex PCR Streptococcus pneumoniae, Haemophilus influenzae and Neisseria meningitidis were enrolled. CSF collected from eligible children were tested by microscopy, culture, soluble antigen at CHUMET laboratory. Residual CSF was referred to the regional reference laboratory (RRL) for real-time polymerase chain reaction (RT-PCR) confirmatory testing and serotyping. Results: Over the 6-year study period, 2286 CSF were tested by PCR, 141 (6.1%) were positive. The age group of (1-12 months) was the most affected (68.0%). The majority of CSF were cloudy with pleiocytosis >100/mm3. Hyperproteinorrhea >1 g/l was noted in 48.2% of cases. The sensitivity of gram stain was respectively 56.6% and 75% for Pneumococcus and Meningococcus detection while for culture it was 28.3% and 66.6%, respectively. The average white cell count was notably higher in meningococcal meningitis and changed significantly according to the pathogens identified (p=0.007). Conclusions: Paediatric bacterial meningitis diagnosis are based on CSF laboratory testing. Accessibility to multiplex PCR point-of-care tests targeting meningitis pathogens should be made easier for laboratories in low-income countries to improve patient care, monitor pathogen trends and vaccine impact program. .